Viewport: An object-oriented approach to integrate workstation software for tile and stack mode display - Ghosh, Srinka (Springer-Verlag, 1997)
Diagnostic workstation design has migrated towards display presentation in one of two modes: tiled images or stacked images. It is our impression that the workstation setup or configuration in each of these two modes is rather distinct. We sought to establish a commonality to simplify software design, and to enable a single descriptor method to facilitate folder manager development of “hanging” protocols. All current workstation designs use a combination of “off-screen” and “on-screen” memory whether or not they use a dedicated display subsystem, or merely a video board. Most diagnostic workstations also have two or more monitors. Our central concept is that of a “logical” viewport that can be smaller than, the same size as, or larger than a single monitor. Each port “views” an image data sequence loaded into offscreen memory. Each viewport can display one or more images in sequence in a one-on-one or traditionally tiled presentation. Viewports can be assigned to the available monitor “real estate” in any manner that fits. For example, a single sequence computed tomography (CT) study could be displayed across all monitors in a tiled appearance by assigning a single large viewport to the monitors. At the other extreme, a multisequence magnetic resonance (MR) study could be compared with a similar previous study by assigning four viewports to each monitor, single image display per viewport, and assigning four of the sequences of the current study to the left monitor viewports, and four of the earlier study to the right monitor viewports. Ergonomic controls activate scrolling through the off-screen image sequence data. Workstation folder manager hanging protocols could then specify viewports, number of images per viewport, and the automatic assignment of appropriately named sequences of current and previous studies to the viewports on a radiologist-specific basis. Furthermore, software development is simplified by common base objects and methods of the tile and stack modes. Prototype workstation display software and folder manager protocol implementation will be described and demonstrated.